PENGOLAHAN DATA EKSPOR TERHADAP RAGAM PRODUK KELAPA SAWIT MENGGUNAKAN METODE ASSOCIATION RULES - Robert Robert; Siti Aisyah; Sasmita Rahmawati Zebua (Politeknik Bisnis Indonesia, 2023)
Palm oil is used as a raw material for producing cooking oil, industrial oil, and fuel. Indonesia is the largest producer of palm oil in Indonesia. One of a company engaged in the production of palm oil is PT Permata Hijau Group. The company produces a wide range of palm oil products from from Palm Oil, Lauric Oil, Biodiesel, and Fatty Acid Oleo. Look at the variety of products palm oil marketed by PT Permata Hijau Group, it is necessary to do so decision making on palm oil product data. Data mining is applied using the Association Rules method to get support and confidence values, where export data processed using this method can determine which particular refined palm oil products are best-selling in the international market. With the Association Rules method, it is hoped that it can help provide an overview for a company in determining the amount of production of certain types of refined palm oil, so crises or excesses of certain processed palm products can be avoided. In this study, the results of data visualization using the Python Library (Matplotlib & Seaborn), products with the item set Glycerine→Stearic Acid and Glycerine-RBDPO→Stearic Acid are the combination of Association Rules that appear most frequently, with 100%. Whereas the combination HPKO→Stearic Acid meets the Association Rules with a value of 94%, RBDPO-HPKO→Stearic Acid and Fatty Acid- HPKO→Stearic Acid with 90%, Glycerine→RBDPO, Glycerine→RBDPO-Stearic Acid, and Glycerine Stearic Acid→RBDPO with 88%, HPKS→Stearic Acid and RBDPO-Fatty Acid→Stearic Acid with 83%. Therefore, processed coconut Palm Glycerine, RBDPO, Stearic Acid, Fatty Acid, HPKO, and HPKS is a product that satisfies the rules of the association so this result can assist the company in determining the amount of product production given the demand for a combination of various processed coconut products of the palm oil, is higher than the variety of refined palm oil other products.